1990
DOI: 10.1159/000119471
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and EEG Sleep Changes in Primary Dysthymia and Generalized Anxiety: A Comparison with Normal Controls

Abstract: All night EEG sleep recordings and clinical assessments of sleep quality were performed in normal controls, patients with generalized anxiety disorder and primary dysthymia. Patients were selected according to DSM-III R. Changes of sleep architecture, namely a reduction of slow wave sleep, are similar in generalized anxiety and dysthymia. Also the two groups do not exhibit the REM sleep disturbances usually observed in affective illness. Duration and continuity measures are unchanged in dysthymics, but anxious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
0
16
1
2
Order By: Relevance
“…High comorbidity with major depression has generated interest in comparing biological markers of the disorders. Latency to REM sleep was normal in these studies, in contrast to findings from major depression where REM sleep latency is reduced (11,12,13).…”
Section: Sleep In Generalized Anxiety Disordercontrasting
confidence: 72%
See 1 more Smart Citation
“…High comorbidity with major depression has generated interest in comparing biological markers of the disorders. Latency to REM sleep was normal in these studies, in contrast to findings from major depression where REM sleep latency is reduced (11,12,13).…”
Section: Sleep In Generalized Anxiety Disordercontrasting
confidence: 72%
“…Studies utilizing objective sleep recordings corroborate the reported associations of GAD and insomnia by demonstrating impaired sleep initiation and maintenance in persons with GAD (11,12,13). High comorbidity with major depression has generated interest in comparing biological markers of the disorders.…”
Section: Sleep In Generalized Anxiety Disordermentioning
confidence: 74%
“…Physical deconditioning was demonstrated in some studies in CFS [38]. Elective stage 4 impairment without stage 3 involve ment is not specific for CFS since this was also reported in MD, GAD and dysthymia [39][40][41], Alpha intrusion in NREM sleep rather than SWS duration per se could per haps have physiopathological relevance in FM and CFS. Studies about alpha sleep in CFS showed conflicting results [6.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, a small study (Arriaga 1991) reported that EEG sleep recordings of participants with primary dysthymia showed reduced slowwave sleep and absence of REM sleep disturbances. These indicate that biologically, primary dysthymia may be closer to generalised anxiety disorder than to affective disorder.…”
Section: Anxiety Disordersmentioning
confidence: 99%